Immunogenicity Monitoring System Incorporating Microfluidic Cell Chip and Paper-based Analytical Device - Lee, Kyung Won; Kyeong Yang, Eun; Yoon, Hyun Chul (2023 22nd International Conference on Solid-State Sensors, Actuators and Microsystems, Transducers 2023, 2023)
With the development of microfluidic chips, there are increasing attempts to integrate cell culture and biomaterial test functions into one chip to supplement experimental animal models [1]. In this study, we developed a simple and easy-to-handle immunogenicity-testing cell chip to evaluate the immunogenicity of biomaterials. On this chip, macrophages were introduced as immunogenicity indicators, and a micro-paper-based analytical device (PAD) was used for optical transducer. In the cell chamber of the developed cell chip, macrophages grow and react to foreign biomaterials. Immune-activated macrophages secrete hydrogen peroxide, which is then transferred to the PAD with single-finger actuation. The hydrogen peroxide molecules reaching the PAD detection zone react with the colorimetric detection substrate, resulting in a color that corresponds to the hydrogen peroxide concentration. With the developed testing chip, the immunogenicity of biomaterials can be determined before administration.
Keywords: Cell Metabolite Transducer; Colorimetric Sensing; Immunogenicity Monitoring; Paper-Based Analytical Device